2002
DOI: 10.1016/s0008-6363(01)00496-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C- or RhoA-induced Ca2+ sensitization in stretch-induced myogenic tone

Abstract: Our results are consistent with important roles for PKC and RhoA in the generation of myogenic tone. Furthermore, enhanced phosphorylation of the myosin light chains by activation of PKCalpha and/or RhoA may be key mechanisms for the Ca(2+) sensitization associated myogenic tone in basilar vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 30 publications
9
61
0
Order By: Relevance
“…PKCε has also been suggested to mediate Ca 2+ sensitization (14) although there are some reports against it (39,40). The present study did not directly explore the possible involvement of PKCε in the pressure-induced Ca 2+ sensitization.…”
Section: +mentioning
confidence: 75%
“…PKCε has also been suggested to mediate Ca 2+ sensitization (14) although there are some reports against it (39,40). The present study did not directly explore the possible involvement of PKCε in the pressure-induced Ca 2+ sensitization.…”
Section: +mentioning
confidence: 75%
“…68,69 Experiments to determine the relative importance of PA SMC versus other cell types in the observed cytoprotective effects of NEP are being developed. In addition, we are expanding the current observations made in mice to the study of relevant human disease states.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated that exposure of mouse cortical brain slices to hypoosmosis stimulated ROS production, which was absent in brain slices from p47phox knockout animals, suggesting that PKC-induced p47phox phosphorylation had a pivotal role in osmotic stress-induced Nox activation in astrocytes (Reinehr et al, 2007). It is noteworthy that several lines of study have demonstrated that PKC activation can be observed after exposing cells to a variety of stress stimuli (for example, cytotoxic chemicals, physical stretch, osmotic shock, hypoxia, and inflammatory cytokines) (Kugiyama et al, 1992;Rzymkiewicz et al, 1996;Goldberg et al, 1997;Liu and Huang, 1997;Schanne et al, 1997;Wyatt et al, 1997;Deng and Poretz, 2002;Motley et al, 2002;Suzuma et al, 2002;Yeon et al, 2002;Liu et al, 2003), and PKC may be viewed as a stress sensor in some circumstances (Barnett et al, 2007). If PKC is indeed involved in Nox activation in acute stress responses, the specific roles of different PKC isoforms need to be defined.…”
Section: B Protein Kinase C-mediated Phosphorylationmentioning
confidence: 99%